2018
DOI: 10.1051/0004-6361/201731363
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the Milky Way’s inner disk and bulge populations: Implications for gas accretion, (the lack of) inside-out thick disk formation, and quenching

Abstract: We show that the bulge and the disk of the Milky Way (MW) at R 7 kpc are well described by a unique chemical evolution and a two phase star-formation history (SFH). We argue that the populations within this inner disk, not the entire disk, are the same, and that the outer Lindblad resonance (OLR) of the bar plays a key role in explaining this uniformity. In our model of a two phase star formation history, the metallicity, [α/Fe] and [α/H] distributions, and age-metallicity relation are all compatible with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
77
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 179 publications
(344 reference statements)
15
77
2
Order By: Relevance
“…The most massive mergers these galaxies experience since z ∼ 3.5 are <1:20 mergers, which is broadly consistent, although on the low mass end, with respect to recent estimates of a Gaia Sausage/Enceladus-type merger for the Milky Way 11 (e.g. Haywood et al 2018a;Helmi et al 2018;Belokurov et al 2019;Deason et al 2019; see also Bignone et al 2019). These 10 We note that the bars in our sample tend to form soon after a merger, since mergers increase the disc mass, and can also remove angular momentum from the disc thus kick-starting the formation of the bar (we will discuss in more detail the mechanisms responsible for bar formation in Auriga galaxies in Fragkoudi et al in prep.).…”
Section: Formation Histories Of Barred-b/p Galaxiessupporting
confidence: 86%
See 2 more Smart Citations
“…The most massive mergers these galaxies experience since z ∼ 3.5 are <1:20 mergers, which is broadly consistent, although on the low mass end, with respect to recent estimates of a Gaia Sausage/Enceladus-type merger for the Milky Way 11 (e.g. Haywood et al 2018a;Helmi et al 2018;Belokurov et al 2019;Deason et al 2019; see also Bignone et al 2019). These 10 We note that the bars in our sample tend to form soon after a merger, since mergers increase the disc mass, and can also remove angular momentum from the disc thus kick-starting the formation of the bar (we will discuss in more detail the mechanisms responsible for bar formation in Auriga galaxies in Fragkoudi et al in prep.).…”
Section: Formation Histories Of Barred-b/p Galaxiessupporting
confidence: 86%
“…This suggests a stellar mass ratio of ∼ 1 : 20 for the recently proposed Gaia Sausage/Enceladus merger (see e.g. Haywood et al 2018a;Helmi et al 2018;Di Matteo et al 2018;Belokurov et al 2019 and see Sections 5.2 and 6).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In particular, as it became clear after Gaia DR2, the Milky Way suffered a large collision with another dwarf Galaxy, the socalled Gaia-Enceladus (Helmi et al 2018) or Gaia-Sausage (Belokurov et al 2018), roughly estimated to have happened around 10 Gyrs ago, contributing to the halo and/or thick disc population observed today (Haywood et al 2018;Sahlholdt et al 2019;Di Matteo et al 2019;Mackereth et al 2019b;Deason et al 2019;Mackereth & Bovy 2020). However, many questions remain open, namely: What was the state of the Milky Way when these mergers occurred?…”
Section: Introductionmentioning
confidence: 99%
“…From the colour-magnitude diagram (CMD) analysis of stars within 2 kpc from the Sun, Gallart et al (2019) suggested that the components of the double sequence observed in the CMD of a sample of kinematically-defined halo stars are coeval but have different metallicity, with the bluer sequence being associated with the accretion event (e.g. Helmi et al 2018;Belokurov et al 2018;Haywood et al 2018). The ages inferred by comparing stellar-model tracks to observed quantities in the CMD suggest a sharper halo age cut around 10 Gyr upon the major accretion event to the MW, while these authors also suggested the thick disc component to be younger.…”
Section: Introductionmentioning
confidence: 99%